2022
DOI: 10.2174/1871520621666210504082528
|View full text |Cite
|
Sign up to set email alerts
|

Propolis Extract Regulates microRNA Expression in Glioblastoma and Brain Cancer Stem Cells

Abstract: Background: Grade IV gliomas are classified as glioblastoma (GBM), which is the most malignant brain cancer type. Various genetic and epigenetic mechanisms play a role in the initiation and progression of GBM. MicroRNAs (miRNAs) are small, non-coding RNA molecules that are the main epigenetic regulatory RNA class. They play variable roles in both physiological and pathological conditions, including GBM pathogenesis, by regulating expression levels of the target genes. Brain cancer stem cells (BCSCs) are subpop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…Nosratiyan et al (2021) and Shao et al (2021) demonstrated that propolis can be used in regenerative medicine as it induced axon myelination and oligodendrocyte progenitor cells (OPC) differentiation. Propolis was also shown to be cytotoxic towards cancerous brain cells, i.e., glioblastoma cells, astrocytes, and astroglial cells [50][51][52]54]. However, Kalia et al (2014) observed no cytotoxicity in organs, including the brain of normal mice fed up to 1000 mg propolis extract/ kg body weight.…”
Section: Discussionmentioning
confidence: 99%
“…Nosratiyan et al (2021) and Shao et al (2021) demonstrated that propolis can be used in regenerative medicine as it induced axon myelination and oligodendrocyte progenitor cells (OPC) differentiation. Propolis was also shown to be cytotoxic towards cancerous brain cells, i.e., glioblastoma cells, astrocytes, and astroglial cells [50][51][52]54]. However, Kalia et al (2014) observed no cytotoxicity in organs, including the brain of normal mice fed up to 1000 mg propolis extract/ kg body weight.…”
Section: Discussionmentioning
confidence: 99%
“…Telomerase activation in cancer has been attributed to several mechanisms, including the involvement of oncogenes like Wnt, which serve as transcriptional regulators of telomerase [ 148 ]. The ability of Aydın Turkish propolis to modulate the expression of microRNAs in glioblastoma and brain cancer stem cells underscores its anticancer effect, with the WNT and NOTCH pathways being implicated [ 152 ].…”
Section: Telomere Lengthmentioning
confidence: 99%
“…Nevertheless, providing rats with propolis extract prior to antineoplastic agent injections shielded the heart and liver tissues from mitochondrial stress [ 221 ]. Studies have suggested that apoptosis stands out as the primary process by which propolis demonstrates its antitumor effects [ 152 , 222 , 223 , 224 ]. In the course of apoptosis, the mitochondrial membrane potential is compromised by the establishment of permeability transition pores.…”
Section: Mitochondriamentioning
confidence: 99%
“…In this study, they identified the role of two new miRNAs, miR-30d-5p and miR-335-5p, that were not reported previously in brain cancer studies. The propolis treatment decreased the expression of miR-30d-5p, a potential oncomir in GBM and increased the expression of miR-335-5p, a potential tumor suppressor in GMB [ 167 ]. Altogether, these findings suggest that propolis may have a reverse effect on cancer cell proliferation and progression by targeting oncogenes and tumor suppressor genes or altering miRNA expression.…”
Section: Molecular Mechanisms Of Anticancer Activities Of Propolismentioning
confidence: 99%